Organisasi Penegak Republik Indonesia Wajo (1945-1950) - Muhammad Hidayatullah; Darman Manda; Ahmadin Ahmadin; Najamuddin Najamuddin (Universitas Negeri Makassar, 2022)
Republic Of Indonesia Wajo Enforcement Organization (1945-1950). This study aims to determine the process of establishing the PRIW organization, the dynamics of the PRIW organization and the influence of the existence of the PRIW organization. The theory used is the theory of structuration proposed by Anthony Giddens. The research method used in this research is historical research method which includes heuristics, source criticism, interpretation, and historiography. In this research, it was found that the establishment of the PRIW organization was initiated from a disagreement between members of Petta Wajo regarding the direction of support from the Wajo Kingdom which caused Andi Ninnong to establish PRIW. Limited logistics and weapons as well as military human resources caused PRIW's steps to stagnate, which eventually regressed and split. The influence of the PRIW organization is the disruption of NICA's activities in Wajo and its surroundings, as well as the position that PRIW's management in Wajo has obtained after Indonesia's independence. It can be concluded that the existence of PRIW is less effective against NICA in Wajo due to several unfavorable factors. Organisasi Penegak Republik Indonesia Wajo (1945-1950). Penelitian ini bertujuan untuk mengetahui proses berdirinya organisasi PRIW, dinamika organisasi PRIW dan pengaruh keberadaan organisasi PRIW. Teori yang digunakan adalah teori strukturasi yang dikemukakan oleh Anthony Giddens. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian sejarah yang meliputi heuristik, kritik sumber, interpretasi, dan historiografi. Dalam penelitian ini diketahui bahwa pendirian organisasi PRIW adalah berawal dari adanya ketidak sejalanan antara anggota Petta Wajo terkait arah dukungan Kerajaan Wajo yang menyebabkan Andi Ninnong mendirikan PRIW. Keterbatasan logistik dan persenjataan dan SDM militer menyebabkan langkah PRIW stagnan yang akhirnya mengalami kemunduran dan terpecah. Pengaruh organisasi kelasykaran PRIW adalah terganggunya kegiatan NICA di Wajo dan sekitarnya, serta adanya jabatan yang didapatkan pengurus PRIW di Wajo setelah Indonesia merdeka sepenuhnya. Hal ini dapat disimpulkan bahwa keberadaan PRIW kurang efektif melawan NICA di Wajo karena beberapa faktor yang kurang mendukung.